Tasawuf Jalaluddin Ar-Rumi Perspektif Annemarie Schimmel - M. Maulana Marsudi (Al Hikmah, 2017)
Most of Orientalis misunderstood about Islam like they were made to touch an elephant, each described it according to the part of body his hands had touched: to one the elephant appeared like a throne, to another like a fan, or like water pipe, or like a pillar. Schimmel attempt to understands of Islam (sufism) very well used Phenomenology Approach, and the result is amazed the others orientalist and most of moslem. Schimmel said thatt the plurality of signs is necessary to veil the eternal One who is transcendent and yet ‘closer than the neck vein’ (QS 50:16). The signs show the way into His presence, where the believer may finally leave the images behind. Rumi one of Sufis who completed that understading passed way divine love.